Spatial and functional changes in recent urban development of Zagreb - Sić, Miroslav (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2007)
This article discusses the urban development of Zagreb in the transition period. It analyses four processes which have caused spatial and functional changes in the cityćs development within its administrative limits. These are: the process of a new CBD establishment, expansion of hypermarkets and commercial centres, housing construction under new conditions and transportation problems and solutions. Under the influence of these processes the spatiofunctional structure of the city becomes more and more complex. In this connection the city has started to have more influence on the urban regions development.
Keywords: Zagreb; urbana geografija; urbani razvoj; mestne četrti; mestni predeli; funkcije; diferenciacija